PENINGKATAN KOLABORASI SISWA PADA MATERI LINGKARAN MELALUI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER - Nurbani; Agung Hartoyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study refers to the low level of student collaboration in mathematics learning. The purpose of writing this article is based on the lack of interaction and role of students in the mathematics learning process on the circle material. Students just sit, keep quiet, listen to the teacher's explanation (teacher centered), so that students are not ready to master the learning material. Where students only learn with a memorization system so that mathematics learning becomes less meaningful. This study aims to improve student collaboration on circle material through the Numbered Head Together (NHT) learning model. This study uses a classroom action research (CAR) method with the Kurt Lewin model consisting of two meetings. Research data were collected using observation and tests. The results showed an increase in student collaboration after the application of the NHT learning model. At meeting I, the percentage of students was only 47%, increasing to 78.4% at meeting II. Thus, the NHT learning model has proven effective in improving collaboration on circle material.